Investigation of space dependence of plasma parameters in multislit electromagnetic trap “Jupiter 2M” - Lavrent’ev, O.A.; Maslov, V.A.; Nozdrachev, M.G.; Oboznyi, V.P.; Skibenko, A.I.; Fomin, I.P. (Вопросы атомной науки и техники, 2003)
The experimental researchs of a transitive layer structure in the multislit electromagnetic trap “Jupiter 2M” are offered in the article. The dependencies of average plasma density on a magnetic field, energy and current of injected electrons, the spatial distributions of plasma density and volumetric charge potential are measured. The border of superseded magnetic field is determined. В роботі представлені експериментальні дослідження структури перехідного шару в багатощілинній електромагнітній пастці “Юпітер 2М”. Виміряні залежності середньої густини плазми від напруженості магнітного поля, енергії та струму інжектованих електронів, радіальні профілі густини плазми і потенціалу об’ємного заряду, визначена межа витісненого магнітного поля. В работе представлены экспериментальные исследования структуры переходного слоя в многощелевой электромагнитной ловушке «Юпитер 2М». Измерены зависимости средней плотности плазмы от напряженности магнитного поля, энергии и тока инжектированных электронов, радиальные профили плотности плазмы и потенциала объемного заряда, определена граница вытесненного магнитного поля.